ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGELOLAAN KEUANGAN PADA REMAJA SMA DI DESA DUWET SITUBONDO DENGAN INKLUSI KEUANGAN SEBAGAI VARIABEL MEDIASI - Zainiyah, Siti; Karnadi, Karnadi; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2023)
The research objective was to determine the Analysis of the Factors Influencing Financial Management in High School Youth in Duwet Situbondo Village with Financial Inclusion as a Mediation Variable. In this study the sampling technique used was Saturated Sample with a total sample of 78. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM).The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that financial literacy has a positive and significant effect on financial inclusion, financial attitudes have a positive and significant effect on financial inclusion, financial literacy has a positive and significant effect on financial management, financial attitudes have a negative but significant effect on Financial management, financial inclusion has a positive and significant effect on financial management, financial inclusion has a positive but not significant effect on financial management through financial inclusion, financial attitudes have a positive and significant effect on financial management through financial inclusion.